Strategisches Management mit Hilfe von Balanced Scorecard. - Schneeberger, Hannes; Scharwitzl, Susanne (Alba, 2008)
Um dem Anspruch eines effizienten Personennahverkehrs gerecht zu werden, haben die Wiener Linien in den letzten Jahren eine Reihe von organisatorischen Maßnahmen ergriffen und ein Konzept zur strategischen Weiterentwicklung entwickelt. Die Balanced Scorecard (BSC) wurde dabei als strategisches Managementinstrument implementiert. Der vorliegende Beitrag zeigt wie ausgehend von der Frage: Wie erreichen wir unser Zukunftsbild? konkrete Aktionen und Maßnahmen abgeleitet werden und wie die BSC im Planungsprozess der Wiener Linien verankert ist.

A series of organisational measures has been taken by Wiener Linien during the last years to meet the high expectations towards public transport in Vienna. Beyond these, a concept for strategic advancement of the company has been developed. In doing so the Balanced Scorecard (BSC) was implemented as a strategic management tool by Wiener Linien. The given article presents how - based on the question: How can we achieve our vision? - precise actions and measures are deduced and how the BSC is positioned in the planning process of Wiener Linien.
Balanced Scorecard as a tool for strategic management.
Keywords: Verkehr; Stadtverkehr; ÖPNV; Verkehrsaufkommen; Verkehrsmittelwahl; Verkehrsunternehmen; Management; Unternehmensführung; Leitbild; Kennwert; Strategisches Management; Managementsystem; Balanced Scorecard